Obrazy miłości - funkcjonowanie pojęć "eros", "agape", "philia" i ich wpływ na postrzeganie miłości w wybranej twórczości Karola Wojtyły - Jana Pawła II = Images of love - concepts of "eros", "agape", "philia" and their impact on the perception of love in the selected works of Karol Wojtyla - John Paul II - Naplocha, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article has been taken to describe the principles of operation of the Greek concepts of "eros", "agape", "philia" and characterize their impact on the perception of love in the selected writings of Karol Wojtyla ? John Paul II. Based on two literary works of Karol Wojtyla: "The Jeweller`s Shop" and "The love and the responsibility", strives to portray the transformation in definition of the concept of "love".
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; literatura polska - 20 w. - tematyka; Polish literature - 20 century - themes; miłość; love